Thiazolidine-2, 4-dione framework containing spiropyrrolidine-oxindole and 1, 2, 3-triazole scaffold: synthesis, in vitro α-amylase inhibition and in silico studies. (28th February 2023) - Duhan, Meenakshi; Singh, Rahul; Devi, Meena; Sindhu, Jayant; Kumar, Parvin; Kumar, Sudhir; Kataria, Ramesh; Kumar, Ashwani; Lal, Sohan; Singh, Devender
Abstract : This study aimed to synthesize thiazolidine-2, 4-dione hybrids followed by evaluating their α-amylase inhibition using in vitro and in silico approaches. Abstract : In an attempt to develop novel α-amylase inhibitors, a series of 2, 4-thiazolidinedione fused spiropyrrolidine-oxindole and 1, 2, 3-triazole scaffolds were designed, synthesized via a multi-component approach and characterized using IR, 1 H NMR, 13 C NMR and DEPT based spectral studies. The exact structure of 9a was confirmed using single-crystal X-ray diffraction studies. The presence of various non-covalent interactions in the molecular structure of 9a was explored using Hirshfeld surface and PARST analysis. All of the synthesized compounds were assessed for in vitro α-amylase inhibition using acarbose as a positive standard. Compound 9b depicted maximum inhibition; 88.05 ± 2.51%, 76.65 ± 2.19% and 68.57 ± 1.96% inhibition at 50, 25 and 12.5 μg mL −1, respectively, relative to standard drug acarbose (77.96%, 71.17% and 67.25%, at 50, 25 and 12.5 μg mL −1 concentration). In silico docking simulations were used to investigate the binding of the compounds within the binding pocket of α-amylase (PDB ID : 7TAA ). Molecular dynamic simulations revealed the stability of the docked ligand–protein complexes.